Transporte eletrônico em anéis quânticos de grafeno - Sousa, Duarte José Pereira de (2015)
In this work, we propose a current switch device that exploits the phase acquired by a charge carrier as it tunnels through a potential barrier in graphene in the ballistic regime without the need of the presence of a gap in the spectrum. The system acts as an interferometer based on an armchair graphene quantum ring, where the phase difference between interfering electronic wave functions for each path can be controlled by tuning the height of a potential barrier in the ring arms. By varying the parameters of the potential barriers the interference can become completely destructive. We demonstrate how this interference effect can be used for developing a simple graphene-based logic gate.